Woven bone formation and mineralization by rat mesenchymal stromal cells imply increased expression of the intermediate filament desmin - Di Conza, Giusy; Barbaro, Fulvio; Zini, Nicoletta; Spaletta, Giulia; Remaggi, Giulia; Elviri, Lisa; Mosca, Salvatore; Caravelli, Silvio; Mosca, Massimiliano; Toni, Roberto (Frontiers in Endocrinology, 2023)
ABSTRACT Background: Disordered and hypomineralized woven bone formation by dysfunctional mesenchymal stromal cells (MSCs) characterize delayed fracture healing and endocrine - metabolic bone disorders like fibrous dysplasia and Paget disease of bone. To shed light on molecular players in osteoblast differentiation, woven bone formation, and mineralization by MSCs we looked at the intermediate filament desmin (DES) during skeletogenic commitment of rat bone marrow MSCs (rBMSCs), where its bone-related action remains elusive. Results. Monolayer cultures of immunophenotypically- and morphologically - characterized, adult male rBMSCs showed co-localization of desmin (DES) with vimentin, F-actin, and runx2 in all cell morphotypes, each contributing to sparse and dense colonies. Proteomic analysis of these cells revealed a topologically-relevant interactome, focused on cytoskeletal and related enzymes / chaperone / signalling molecules linking DES to runx2 and alkaline phosphatase (ALP). Osteogenic differentiation leaded to mineralized woven bone nodules confined to dense colonies, significantly smaller and more circular with respect to controls. It significantly increased also colony-forming efficiency and number of DES-immunoreactive dense colonies, and immunostaining of co-localized DES / runx-2 and DES / ALP. These data confirmed pre-osteoblastic and osteoblastic differentiation, woven bone formation, and mineralization, supporting DES as a player in the molecular pathway leading to the osteogenic fate of rBMSCs. Conclusions. Immunocytochemical and morphometric studies coupled to proteomic and bioinformatic analysis supports the concept that DES may act as an upstream signal for the skeletogenic commitment of rBMSCs. Thus, we suggest that altered metabolism of osteoblasts, woven bone, and mineralization by dysfunctional BMSCs might early be revealed by changes in DES expression / levels. Non-union fractures and endocrine – metabolic bone disorders like fibrous dysplasia and Paget disease of bone might take advantage by this molecular evidence for their early diagnosis and follow-up .